Demplot Budi Daya Lobster dan Kerang Mutiara secara Terintegrasi dalam Rangka Penguatan Kemitraan Masyarakat Lombok Utara - Muhamad Junaidi; Bagus Dwi Hari Setyono; Fariq Azhar (Institut Pertanian Bogor, 2020)
Integrated Community Partnership Program (PKM) activities of lobster and pearl shells with the aim of increasing marine aquaculture production through the application and development of integrated aquaculture technologies. In addition, this activity is expected to increase knowledge and skills in productive economic business activities. In addition, this activity is expected to increase knowledge and skills in productive economic business activities. The method of implementing PKM is the method of demonstration plot, where the target community groups play an active role at all stages of activities. Implementation of activities offered to support the realization of PKM activities with steps that have been mutually agreed upon include strengthening and socializing PKM activities, training, strengthening institutional management, demonstration plots of integrated system cultivation and coaching and mentoring. The results of PKM activities provide a positive value for the target community, with integrated aquaculture production of floating net cages (KJA) in the sea no longer relying on one commodity, but one KJA unit can produce two commodities namely lobster (Panulirus homarus) and pearl shells (Pinctada maxima). Thus the potential to provide additional income for the community from these two commodities. In addition, through this PKM activity, it is expected that the knowledge and skills of the target communities will increase in order to strengthen community partnerships.